Multiparametric magnetic resonance imaging to characterize cabotegravir long‐acting formulation depot kinetics in healthy adult volunteers. Issue 4 (31st July 2021) - Jucker, Beat M.; Fuchs, Edward J.; Lee, Sarah; Damian, Valeriu; Galette, Paul; Janiczek, Robert; Macura, Katarzyna J.; Jacobs, Michael A.; Weld, Ethel D.; Solaiyappan, Meiyappan; D'Amico, Ronald; Shaik, Jafar Sadik; et al.
Abstract : Aim: Cabotegravir long‐acting (LA) intramuscular (IM) injection is being investigated for HIV preexposure prophylaxis due to its potent antiretroviral activity and infrequent dosing requirement. A subset of healthy adult volunteers participating in a Phase I study assessing cabotegravir tissue pharmacokinetics underwent serial magnetic resonance imaging (MRI) to assess drug depot localization and kinetics following a single cabotegravir LA IM targeted injection. Methods: Eight participants (four men, four women) were administered cabotegravir LA 600 mg under ultrasonographic‐guided injection targeting the gluteal muscles. MRI was performed to determine injection‐site location in gluteal muscle (IM), subcutaneous (SC) adipose tissue and combined IM/SC compartments, and to quantify drug depot characteristics, including volume and surface area, on Days 1 (≤2 hours postinjection), 3 and 8. Linear regression analysis examined correlations between MRI‐derived parameters and plasma cabotegravir exposure metrics, including maximum observed concentration ( C max ) and partial area under the concentration–time curve (AUC) through Weeks 4 and 8. Results: Cabotegravir LA depot locations varied by participant and were identified in the IM compartment ( n  = 2), combined IM/SC compartments ( n  = 4), SC compartment ( n  = 1) and retroperitoneal cavity ( n  = 1). Although several MRI parameter and exposure metric correlations were determined, total depot surface area on Day 1 strongly correlated with plasma cabotegravir concentration at Days 3 and 8, C max and partial AUC through Weeks 4 and 8. Conclusion: MRI clearly delineated cabotegravir LA injection‐site location and depot kinetics in healthy adults. Although injection‐site variability was observed, drug depot surface area correlated with both plasma C max and partial AUC independently of anatomical distribution.